Introduction to Pharmacology, - Mannfred A Hollinger (CRC Press, 2008)
Advances in pharmacogenomics and proteomics, along with the introduction of recombinant DNA technology, have expanded the applications of pharmacology to encompass a range of disciplines. Biomedical researchers, protein specialists, and molecular biologists are all involved in the development and delivery of novel drugs. Therefore, students in a variety of life sciences now require grounding in pharmacology. Adding much new material, Introduction to Pharmacology, Third Edition familiarizes students with the curative action of specific drugs, along with current research and the multifaceted role of pharmacology in society. New to the third edition Ãƒâ€šÃ,Â· Chapters on smooth muscle pharmacology covering gastrointestinal and pulmonary pharmacology Ãƒâ€šÃ,Â· Pharmacology advances at the molecular level Ãƒâ€šÃ,Â· The historical background of the Watson Crick model of DNA Ãƒâ€šÃ,Â· Cutting edge topics such as RNA interference and dopamine signaling The text begins with a discussion on the absorption, distribution, metabolism, and elimination of drugs. Much emphasis is placed on pharmacokinetic aspects: how drugs produce an effect and the quantification of these effects for comparative purposes. Also the text describes substance abuse pharmacology and the evolution of drug laws. Several chapters deal with the development of drugs and challenges faced in drug discovery. Identifying both the therapeutic and toxicological aspects of drug use, Introduction to Pharmacology employs contemporary examples to help students become familiar with drug development and treatment, as well as possible adverse affects, and the impact of drug research and use on society today and into the future.